Elemental toxicities – adaptive traits governing waterlogging tolerance in wheat (Triticum aestivum) under sodic soils - KULSHRESHTHA, NEERAJ; KUMAR, ASHWANI; PRASAD, K R K; SINGH, MONIKA; KUMAR, RAJESH; BASAK, NIRMALENDU; YADUVANSHI, N P S; SHARMA, P C; SHARMA, S K (The Indian Journal of Agricultural Sciences, 2020)
Wheat (Triticum aestivum L.) is one of the most intolerant crops to soil waterlogging, so to evaluate the response of 10 wheat varieties to waterlogging stress under sodic soils, a pot experiment was conducted during 2011-12, 2012-13 and 2014-15 at ICAR-CSSRI, Karnal. Critically important physiological data on increase in element concentrations of Fe, Mn, Al and B in shoots indicated key mechanisms of tolerance under waterlogging condition in sodic soils. Concentrations of Fe, Mn, Al and B in wheat genotypes were greater under waterlogging in normal and sodic conditions. However, uptakes of these elements also varied. Mean concentrations of 327, 434, 541 and 624 mg/kg for Fe; 38.3, 48.9, 48.4 and 72.9 mg/kg for Mn; 47, 147, 217 and 226 mg/kg for Al and 5, 22, 48 and 51 mg/kg for B were recorded in pH 8.2, pH 8.2 +WL, pH 9.4 and pH 9.4 +WL treatments, respectively. Besides Mn, the elements concentration in wheat was 3-6 times greater than critical limit for the above mentioned elements. Genotype HD 2189, was the best performer and showed minimum increase in shoot Fe, Mn, Al and B concentration both under higher pH and waterlogging, whereas Brookton showed maximum increase. KRL 3-4 performed better despite high Fe and Mn indicating higher tissue tolerance. These observations point towards identification of considerable genetic diversity for Fe, Mn, Al and B in wheat.